The Effect of Celebrity-Program Congruence and Celebrity Credibility on Intention to Watch Sports Video on YouTube - Hanifa Azaria Putri; Catur Sugiarto (Indonesia Marketing Association (IMA), 2023)
YouTube become a business platform for celebrities to gain profits, both in terms of material and popularity. Many celebrities are now establishing companies with their focus centered on the YouTube platform. However, research discussing celebrities as business owners is still limited. Therefore, this study aims to contribute to the development of literature, especially to give a better understanding in the context of the role of celebrity-program congruence and celebrity credibility on intention to watch sports videos on YouTube. An online questionnaire was implemented for information acquisition from 228 respondents. The results showed that celebrity-program congruence positively impacted on celebrity credibility. Celebrity credibility positively impacted on attitude toward the video and intention to watch sports videos on YouTube. Additionally, attitude toward the video positively impacted on the intention to watch sports videos on YouTube. However, celebrity-program congruence does not have an impacted on attitude toward the video and the intention to watch sports videos on YouTube. This study further explains indirect relationships through mediation analysis. A mediation model has been developed to provide a better understanding of the role of attitude toward videos. This study found that attitude toward videos positively mediates the relationship between celebrity credibility on intention to watch sports videos on YouTube.